Interlayer modification and single-layer exfoliation of the Ruddlesden–Popper perovskite oxynitride K2LaTa2O6N to improve photocatalytic H2 evolution activity. Issue 17 (18th April 2023) - Shiroma, Yuta; Mogi, Hiroto; Mashiko, Takeaki; Yasuda, Shuhei; Nishioka, Shunta; Yokoi, Toshiyuki; Ida, Shintaro; Kimoto, Koji; Maeda, Kazuhiko
Abstract : Ethylamine-intercalated H x K2− x LaTa2 O6 N, further modified with a Pt cocatalyst, exhibited 60 times height photocatalytic activity for H2 evolution under visible light, as compared with the parent layered material. Abstract : Modification of the interlayer nanospaces of lamellar solids is an effective means of enhancing the physical properties and chemical functions of such materials. The present work demonstrates the interlayer modification of the layered perovskite oxynitride K2 LaTa2 O6 N, a photocatalyst having a ∼600 nm absorption edge and exhibiting visible-light-driven H2 evolution activity. This material was subjected to various interlayer modifications, including H + /K + exchange, ethylamine (EA) intercalation and exfoliation with tetra( n -butyl)ammonium hydroxide (with subsequent restacking) while maintaining its capacity for visible light absorption. H2 evolution activity from aqueous methanol with the aid of an optimal amount of a Pt cocatalyst was improved by a factor of approximately 60 following EA intercalation to increase the interlayer spacing of the host material. However, subsequent exfoliation-restacking to yield flocculated nanosheets led to a decrease in activity as compared with the EA-intercalated specimen. The present results indicate that the intercalation of EA provided interlayer nanospaces suitable for Pt cocatalyst loading and so promoted the photocatalytic H2 evolution reaction, while the restacked nanosheets did not provide space for Pt loading.